To Assess the Outcome of Low Molecular Weight Heparin for Management of Females Presenting with Placental Insufficiency - Munazzah Nisar, Saleha Ijaz, Samara Kaleem, Amna Parveen, Maria Maqsood, Asima Iftikhar, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Placental insufficiency is a serious condition that affects pregnant women and can lead to a range of complications during pregnancy. One potential treatment for this condition is the use of low molecular weight heparin. Objectives: The main objective of the study is to assess the outcome of low molecular weight heparin for management of females presenting with placental insufficiency. Material and methods: This descriptive case series was conducted in Unit II, Department of Obstetrics & Gynecology, Lady Willingdon Hospital, Lahore. Sample size of 175 cases was calculated with 95% confidence level, 4.5% margin of error and taking expected percentage of SGA i.e. 10.1% with LMWH in females placental insufficiency. Data was collected through non-probability consecutive sampling technique. Results: In this present study total 175 females were enrolled. The mean age of the females was 29.70±6.36 years with minimum and maximum ages of 20 & 40 years respectively. In this study the mean gestational age of the females was 33.99±1.43 weeks with minimum and maximum values of 32 & 36 weeks respectively. 35(20%) females had null parity, 37(21.14%) females had primary, 45(25.71%) females had secondary parity and rest of the females belonged to multiple parity. Practical implication: This study will be helpful in finding outcome by LMWH for management of females presenting with placental insufficiency Conclusion: According to this study the outcome by LMWH for management of females presenting with placental insufficiency showed preterm delivery in 26.9% and SGA in 8% females. Keywords: LMWH, Delivery, Patients, Pregnant, Treatment, Weight